Immunotherapy with oral administration of humanized anti‐CD3 monoclonal antibody: a novel gut‐immune system‐based therapy for metaflammation and NASH. (21st September 2018) - Ilan, Y.; Shailubhai, K.; Sanyal, A.
Summary: The immune system plays a role in the pathogenesis of non‐alcoholic steatohepatitis (NASH) underlying hepatocyte injury and fibrosis progression at all disease stages. Oral administration of anti‐CD3 monoclonal antibody (mAb) has been shown in preclinical studies to be an effective method for systemic immune modulation and alleviates immune‐mediated disorders without T cell depletion. In the present review, we summarize the concept of the oral administration of humanized anti‐CD3 mAb in patients with NASH and discuss the potential of this treatment to address the current requirements of treatments for NASH. Recently published preclinical and clinical data on oral administration of anti CD3 are discussed. Human trials have shown that the oral administration of anti‐CD3 in healthy volunteers, patients with chronic hepatitis C virus (HCV) infection and patients with NASH and type 2 diabetes is safe and well tolerated, as well as biologically active. Oral anti‐CD3 induces regulatory T cells, suppresses the chronic inflammatory state associated with NASH and exerts a beneficial effect on clinically relevant parameters. Foralumab is a fully human anti‐CD3 mAb that has recently been shown to exert a potent anti‐inflammatory effect in humanized mice. It is being developed for treatment of NASH and primary biliary cholangitis (PBC). Oral administration of anti CD3 may provide an effective therapy for patients with NASH. Abstract : Oral administration of anti‐CD3 monoclonal antibody (mAb) has been shown in pre‐clinical and phase I/IIA clinical studies to be an effective method for systemic immune modulation and alleviates immune mediated disorders without T‐cell depletion. Foralumab is the humanized formulation of anti CD3 antibody.